Evolutionary pathways for deep-sea adaptation in marine planktonic Actinobacteriota - Roda-Garcia, Juan J.; Haro-Moreno, Jose M.; López-Pérez, Mario (Frontiers in Microbiology, 2023)
The deep ocean, one of the largest ecosystems on earth, is dominated by microorganisms that are keystones in the regulation of biogeochemical cycles. However, the evolutionary pathways underlying the specific adaptations required (e.g. high pressure and low temperature) by this unique niche remain understudied. Here, we analyzed the first representatives belonging to the order Acidimicrobiales, a group of marine planktonic Actinobacteriota, that specifically inhabits the aphotic zone of the oceanic water column (>200m). Compared with their epipelagic counterparts, deep-sea representatives showed the same evolution in genome architecture with higher GC content, longer intergenic spaces as well as higher nitrogen (N-ARSC) and lower carbon (C-ARSC) content in encoded amino acid residue side chains consistent with the higher nitrogen concentration and lower carbon concentration in deep waters compared to the photic zone. Metagenomic recruitment showed distribution patterns that allowed the description of different ecogenomic units within the three deep water-associated genera defined by our phylogenomic analyses (UBA3125, S20-B6 and UBA9410). The entire genus UBA3125 was found exclusively associated with oxygen minimum zones linked to the acquisition of genes involved in denitrification. Genomospecies of S20-B6 recruited in samples from both mesopelagic (200-1000 m) and bathypelagic (1000-4000 m) zones, including polar regions. Diversity in the genus UBA9410 was higher, with genomospecies widely distributed in temperate zones, others in polar regions, and the only genomospecies associated with abyssal zones (>4000 m). At the functional level, groups beyond the epipelagic zone have a more complex transcriptional regulation including in their genomes a unique WhiB paralog. In addition, they showed higher metabolic potential for organic carbon and carbohydrate degradation as well as the ability to accumulate glycogen as a source of carbon and energy. This could compensate for energy metabolism in the absence of rhodopsins, which is only present in genomes associated with the photic zone. The abundance in deep samples of cytochrome P450 monooxygenases associated with the genomes of this order suggests an important role in remineralization of recalcitrant compounds throughout the water column.